Struktur Konten Pendidikan Politik dalam Buku Murid Pendidikan Pancasila Tingkat Sekolah Menengah Atas - Ismail Ismail; Nasiwan Nasiwan (Publikasi Indonesia, 2026)
This study aims to analyze the structure of political education content in the Pancasila Education student textbook at the senior high school level. The method used is critical discourse analysis developed by Teun van Dijk, focusing on the text structure within the Pancasila Education student textbook. The findings reveal that the structure of political education content in the Pancasila Education subject at the senior high school level, based on the analysis of macrostructure, superstructure, and microstructure, shows that the political education material in the textbook predominantly emphasizes the Pancasila ideology. The political education content in the textbook is unbalanced, and the discourse on political education presented in the textbook uses an approach based on loyalty and threats to convey its messages. From these findings, it can be concluded that the political education portrayed in the Pancasila Education student textbook is indoctrinative, with a lack of substance in the political education material relevant to current social conditions.